Caracterização epidemiológica dos casos de HIV/aids em pessoas com 60 anos ou mais, Pará: período 2006 – 2015 - OLIVEIRA, Darlene Dias de Sousa Duarte (2019)
Introduction: The Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome (HIV/AIDS) remain a challenge to global public health. The elderly population has been greatly impacted by the HIV/AIDS with a significantly increase of 201.37% in notification in the last ten years. The state of Pará is the seventh among the Brazilian Federal Units with the highest rate of detection of HIV/AIDS. However, this is the first studies about the expression of HIV/AIDS epidemic in elderly living in Pará. Objective: To trace the epidemiological profile of the elderly living with HIV / AIDS in the state of Pará. Materials and methods: It is a descriptive, retrospective and cross–sectional study using secondary data bases of the State Department of Public Health of Pará (SESPA) of HIV/AIDS notifications in the elderly from 2006 to 2015. The data were grouped by counties and the variables “gender, race, exposition groups, school degree and incidence” analyzed and expressed as rate and relative frequency. Results: In the period between 2006 and 2015, 67 municipalities reported cases of HIV / AIDS in elderlies, with total of 338 cases and an increase of 1283.33% on the notifications in the period studied. The male/female ratio was 2.52. The counties that presented notifications the most were Belém (90), Ananindeua (41) and Santarém (16). The highest incidences (/100.000 habitants) were Cumaru do Norte (414.94), Novo Progresso (369.69) and Canaã dos Carajás (333.06). Tucuruí was the only one that presented a reduction on the notification tax (50%). Among men, the category of heterosexual exposure was the most prevalent (78.69%). The majority of the sample had low educational level (57.19%) and were dark–skinned (pardos) (80.77%). Conclusion: The counties with the highest incidence of HIV / AIDS were those with the highest economic developing, suggesting a strong association with the migratory flow of workers associated with the low level of instruction of the population. Sexual health education and access to preventive means, diagnoses and treatments for this specific population need to be implemented.